Measuring Duchenne muscular dystrophy impact: development of a proxy-reported measure derived from PROMIS item banks - Carolyn E. Schwartz (BMC, 2021)
Abstract Background Person-reported outcomes measurement development for rare diseases has lagged behind that of more common diseases. In studies of caregivers of patients with rare diseases, one relies on proxy report to characterize this disability. It is important to measure the child’s disability accurately and comprehensively because it affects caregiver burden. We aimed to create a condition-specific caregiver proxy-report measure for Duchenne Muscular Dystrophy (DMD) in order to understand the impact of DMD on the caregiver. Drawing on relevant item banks from the Patient-Reported Outcome Measurement Information System (PROMIS), we sought to confirm their reliability and validity in the target sample of DMD caregivers. Methods This web-based study recruited DMD caregivers via Rare Patient Voice, patient-advocacy groups, and word of mouth. Recruitment was stratified by age of the caregiver’s child with DMD, which broadly represents stages of DMD progression: 2–7, 8–12, 13–17, and > 18. Telephone interviews with DMD parent-caregivers pretested possible measures for content validity. The web-based study utilized an algorithm to categorize respondents’ ambulatory status for tailored administration of PROMIS Parent-Proxy items as well as some new items developed based on caregiver interviews. Item response theory analyses were implemented. Results The study sample included 521 DMD caregivers representing equally the four age strata. The proxy-report measure included the following domains: fatigue impact, strength impact, cognitive function, upper extremity function, positive affect, negative affect, sleep-device symptoms, and mobility. The first five domains had strong psychometric characteristics (unidimensionality; acceptable model fit; strong standardized factor loadings; high marginal reliability). Negative Affect, covering anger, anxiety, depressive symptoms, and psychological stress, fit a bifactor model with good model fit, high marginal reliability, and strong factor loadings. The Sleep-device symptoms domain was not unidimensional, and the mobility domain did not have a simple structure due to residual correlations among items at opposite end of the mobility-disability continuum. These two domain scores were retained as clinimetric indices (i.e., uncalibrated scales), to achieve the overall goal of having a content-valid DMD-specific measure across all stages of disease severity. Conclusions The present study derived a DMD-specific proxy-report measure from PROMIS item banks and supplemental items that could potentially be utilized in caregiver research across all stages of the care recipient’s DMD. Future research will focus on assessing the responsiveness and validity of the measure over time and its comparison to DMD patient self-report.